Natura czasoprzestrzeni a istnienie zbiorów - Augustynek, Zdzisław (Filozofia Nauki, 1995)
This paper tries to prove two statements. Firstly, that set-theoretic positions in the controversy on the ontic nature of space-time logically imply set-theoretic realism. Secondly, thatmereological positions in this controversy give set-theoretic nominalism an appearance of verisimilitude.